EFFECTIVENESS OF BASIC MATHEMATICS TEACHING MATERIALS STUDY PROGRAM IN INFORMATICS ENGINEERING EDUCATION - Lili Rismaini; Dewi Devita; Syelfia Dewimarni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2022)
Background of this research is based on the difficulty of students understanding the material and knowledge of terms in mathematics that are less familiar in their learning environment so that with the development of this teaching material, it is hoped that student learning outcomes will be more optimal. This study aims to produce basic mathematics teaching materials that are valid and effective in basic mathematics learning. The type of this research is development research with the chosen development model, namely the Smith and Ragan model. This research was carried out on students of the informatics engineering education study program at the University of Putra Indonesia